Learning from crises : Building a resilient future for Pakistan's Tourism - Muhammad Kashif, ,; Mohd Hanafiah, Ahmad; Naushad Sabzwari, Muhammad; Asma, Abdul Karim; Zeb, Alam (IJME, 2024)
Crippled by natural and man-made crises, the tourism industry stands at a crossroads, grappling with the unprecedented challenges of the global pandemic. This qualitative study, based on in-depth interviews with 10 individuals, delves into the resilience factors within Pakistan’s tourism landscape. Our analysis unearths eight core themes – government support, focusing on foreign tourists, proactive planning, technology innovation, domestic tourism, limited-scale opening of tourism, tourism education, and consumer and employee confidence – that form the foundation of a comprehensive resilience framework. This framework functions as a prescriptive roadmap, guiding the tourism industry’s proactive revival in the face of future pandemics and fostering its long-term sustainability in the post-pandemic era. Beyond Pakistan, our study’s inclusive resilience approach offers a transformative model for developing countries, potentially triggering a paradigm shift towards a novel economic framework. This research not only paves the way for the revitalization of tourism in Pakistan but also opens doors for futher exploration of tourism resilience during future crises.